Effects of Calcium Source on Biochemical Properties of Microbial CaCO3 Precipitation - Xu, Jing; Du, Yali; Jiang, Zhengwu; She, Anming (Frontiers in Microbiology, 2015)
The biochemical properties of CaCO3 precipitation induced by Sporosarcina pasteurii, an ureolytic type microorganism, were investigated. Effects of calcium source on the precipitation process were examined, since calcium source plays a key role in microbiologically-induced mineralization. Regardless of the calcium source type, three distinct stages in the precipitation process were identified by Ca2+, NH4+, pH and cell density monitoring. Compared with stage 1 and 3, stage 2 was considered as the most critical part since biotic CaCO3 precipitation occurs during this stage. Kinetics studies showed that the microbial CaCO3 precipitation rate for calcium lactate was over twice of that for calcium nitrate, indicating that calcium lactate is more beneficial for the cell activity, which in turn determines urease production and CaCO3 precipitation. X-ray diffraction analysis confirmed the CaCO3 crystal as calcite, although scanning electron microscopy revealed a difference in crystal size and morphology if calcium source was different. The findings of this paper further suggest a promising application of microbiologically-induced CaCO3 precipitation in remediation of surface and cracks of porous media, e.g. cement-based composites, particularly by using organic source of calcium lactate.